Slope Map between Shackleton and de Gerlache Craters, Lunar South Pole - Harish; Animireddi, Venkata Satya Kumar; Barrett, Natasha; orcid:0000-0002-4964-1138; Boazman, Sarah; Gawronska, Aleksandra; Gilmour, Cosette; orcid:0000-0002-4978-530X; Halim, Samuel; McCanaan, Kathryn; Shah, Jahnavi; Kring, David A. (David Allen); et al. (Center for Lunar Science and Exploration, Lunar and Planetary Institute, 2020)
This map is based on data collected by the Lunar Orbiter Laser Altimeter (LOLA) onboard the Lunar Reconnaissance Orbiter (LRO). The map shows slopes derived from the LOLA 10-m elevation product (NASA Goddard Space Flight Center; Smith et al., 2010; Smith et al., 2017). The slope is represented with four traditional colors 0° to 5° (light green), 5° to 10° (bright green), 10° to 15° (dark green), 15° to 20° (yellow), and >20° (red). The map covers the region between Shackleton and de Gerlache craters. Slope data are overlain on a derived hillshade with solar azimuth 45°W and solar elevation 45°. A product of the Exploration Science Summer Intern Program: Harish, Venkata Satya Kumar Animireddi, Natasha Barrett, Sarah Boazman, Aleksandra Gawronska, Cosette Gilmour, Samuel Halim, Kathryn McCanaan, Jahnavi Shah, and David Kring.